A Gap or Lacuna in the World Anti-Doping Code? Remarks on the CAS Interpretation in IOC, WADA, and ISU v. RUSADA, Kamila Valieva and Russian Olympic Committee (CAS OG 22-08, CAS OG 22-09, and CAS OG 22-10) - Pavot, David (Frontiers in Sports and Active Living, 2022)
This article focuses on the award of 14 February 2022, rendered by the CAS ad hoc chamber in the appeal filed by IOC, ISU and WADA against the decision of the RUSADA Disciplinary Committee lifting the provisional suspension of Kamila Valieva. Kamila Valieva is one of the world's best 15-year-old figure skaters. Prior to the Beijing Olympic Games, she tested positive for a substance prohibited in and out of competition under the WADC and was provisionally suspended. Her suspension was lifted by the RUSADA Disciplinary Committee, and the case was brought before the CAS. Because of her young age, Valieva is a minor and therefore a protected person according to the WADC. The CAS concluded that the Code, by setting up a system of sanctions for these protected persons but not providing for any temporary sanctions, contained a lacuna that it had to fill. However, the identification of the gap and the interpretation of the rules by CAS is questionable in this award.